Automobile suspension spring steel and preparation method thereof
By using a combination of high -strength composite materials and high -entropy alloys in the car suspension spring steel, the problem of short fatigue life, poor corrosion resistance, and difficulty to achieve lightweighting of spring steel are solved. Corrosion resistance and lighter quality.
Patent Information
- Application Number
- CN202411487505.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
AI Technical Summary
Existing automotive suspension spring steels are prone to fatigue damage under long-term repeated loads, resulting in an increase in the risk of fracture. At the same time, they are poor corrosion resistance in corrosive environments of wet and salt spray, making it difficult to achieve lightweight.
采用高强度复合材料和高熵合金相结合的设计,纤维体积分数为55%-65%,树脂基体为35%-45%,纤维层合铺设角度为0°、±45°和90°,并 There is nano -coating on the surface or processing through laser melting technology.
It significantly improves the anti -fatigue performance and corrosion resistance of spring steel, prolongs the service life, reduces damage and failure caused by fatigue, improves the safety and reliability of the car, and achieves lightweight. Essence
Smart Images

Figure CN119371774A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile manufacturing, in particular to automobile suspension spring steel and a preparation method thereof. Background Art
[0002] With the rapid development of the automobile industry, suspension systems, as an important part of automobile safety and comfort, are widely used in various models. The spring steel in the automobile suspension system is subjected to long-term dynamic loads and frequent complex stress cycles, so the requirements for its mechanical properties, durability and environmental adaptability are very high. At present, traditional automobile suspension spring steel mainly uses high carbon steel, manganese steel or stainless steel, and undergoes quenching and tempering heat treatment processes to improve its strength and toughness.
[0003] However, traditional steel springs are prone to fatigue damage under long-term repeated loads, resulting in an increased risk of fracture. The reason is that steel will produce microcracks under repeated dynamic stress. As the cyclic stress increases, these cracks gradually expand and eventually lead to fatigue fracture of the material. In addition, due to the grain structure and internal defects of traditional steel, it is more likely to form stress concentration in high stress areas, further aggravating the initiation and expansion of fatigue cracks, and ultimately shortening the fatigue life of the spring. On the other hand, ordinary steel is prone to corrosion in humid, salt-fog corrosive environments, affecting the service life of the spring. This is because when traditional steel is exposed to moisture or salt in the air, its surface is prone to oxidation reactions and generates corrosion products. These corrosion products not only weaken the integrity of the material surface, but also aggravate stress corrosion, causing microcracks to expand faster in a corrosive environment, resulting in a decrease in spring strength and stiffness. In severe cases, it may break or fail, reducing the overall life of the spring. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an automobile suspension spring steel and a preparation method thereof, which solves the problems of short fatigue life, poor corrosion resistance and difficulty in achieving lightweight of spring steel in the prior art.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A kind of automobile suspension spring steel, including the following materials:
[0006] High-strength composite spring steel, wherein the fiber is carbon fiber or glass fiber, the resin matrix is epoxy resin or thermosetting resin, the fiber volume fraction is 55%-65%, the resin matrix is 35%-45%, and the fiber layer laying angles are 0°, ±45° and 90°;
[0007] High entropy alloy spring steel, its alloying elements include cobalt, chromium, iron, manganese, and nickel, and the content of each element by mass percentage is: cobalt 15%-25%, chromium 15%-20%, iron 20%-25%, manganese 15%-25%, nickel 10%-15%, and trace elements molybdenum and vanadium, whose content is 0.1%-0.5%.
[0008] Preferably, the surface of the high-strength composite spring steel is provided with a nano coating with a thickness of 5-10 μm, and the coating is TiN or SiC nano material.
[0009] Preferably, the surface of the high entropy alloy spring steel is processed by laser cladding technology, the thickness of the cladding layer is 50-100 μm, and the cladding material is a CoCrNi-based alloy.
[0010] A method for preparing automobile suspension spring steel comprises the following steps:
[0011] 1) Preparation of high-strength composite spring steel: carbon fiber or glass fiber and epoxy resin matrix are mixed in a volume fraction ratio of 55%-65% and 35%-45%, layered at angles of 0°, ±45° and 90°, and hot-pressed to obtain composite spring steel;
[0012] 2) preparing high entropy alloy spring steel: weighing raw materials of cobalt, chromium, iron, manganese, nickel and trace amounts of molybdenum and vanadium according to mass percentage, and melting them by vacuum induction melting and casting process to form a high entropy alloy billet;
[0013] 3) Heat treatment and surface strengthening: The high entropy alloy billet is subjected to isothermal quenching and laser surface cladding treatment to enhance the surface strength and corrosion resistance of the material.
[0014] Preferably, the resin viscosity is controlled at 200-300 mPa·s, the temperature of hot pressing is controlled at 180° C., the pressure is 3-5 MPa, and the curing time is 1-2 hours.
[0015] Preferably, the fiber winding process uses a CNC fiber winding device to control the winding angle to be ±45° and the winding tension to be within the range of 10-15N to ensure uniform laying of the fibers.
[0016] Preferably, the vacuum induction melting temperature of the high entropy alloy is 1600-1700°C, and the cooling rate is controlled at 5-10°C / s to optimize the grain structure of the alloy.
[0017] Preferably, the isothermal quenching temperature of the high entropy alloy is 300° C., the holding time is 1 hour, and then it is slowly cooled to room temperature.
[0018] Preferably, in the laser cladding process, the laser power is 800 W, the scanning speed is 10 mm / s, and the cladding thickness is 50-100 μm.
[0019] Preferably, the surface nano coating is formed by physical vapor deposition, and the coating thickness is controlled at 5-10 μm.
[0020] The present invention provides an automobile suspension spring steel and a preparation method thereof, which has the following beneficial effects:
[0021] 1. The present invention greatly improves the fatigue resistance of spring steel by using high-strength composite materials, combined with reasonable fiber layer design and optimized preparation process. Compared with traditional high-carbon steel or manganese steel springs, the springs of the present invention can maintain a longer fatigue life under long-term repeated loads, especially in high-frequency dynamic loads and complex stress environments, which can extend the service life of the spring, reduce damage and failures caused by fatigue, and improve the safety and reliability of the vehicle.
[0022] 2. The present invention significantly improves the corrosion resistance of spring steel in harsh environments by adopting nano-coating technology and laser cladding technology. The TiN or SiC nano-coating coated on the surface of the high-strength composite material, combined with the laser cladding alloy layer on the surface of the high-entropy alloy, enables the spring to exhibit extremely strong corrosion resistance in a humid, salt-fog corrosive environment, preventing material performance degradation and structural damage caused by corrosion, thereby extending the overall service life of the spring.
[0023] 3. The present invention adopts a combination of high-strength composite materials and high-entropy alloys to effectively reduce the weight of the spring and significantly improve the lightweight effect of the automobile suspension system. Compared with traditional steel, the high specific strength of composite materials and high-entropy alloys enables the spring to reduce weight while still maintaining good mechanical properties. Lightweighting not only helps to reduce the overall mass of the car, but also improves fuel efficiency, reduces energy consumption, and enhances the vehicle's power performance and handling flexibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a stereogram of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Please see attached Figure 1The embodiment of the present invention provides a new type of automobile suspension spring steel and a preparation method thereof. The suspension spring steel is based on the innovative design of high-strength composite materials and high-entropy alloys, and provides lightweight, high-strength, corrosion-resistant and fatigue-resistant suspension spring steel by optimizing material composition, layer structure and manufacturing process. The spring steel of the present invention can adapt to complex working environments and meet the high requirements of automobile suspension systems for durability and performance.
[0027] 1. High-strength composite spring steel
[0028] 1.1 Material composition design
[0029] The high-strength composite spring steel of the present invention uses carbon fiber or glass fiber as a reinforcing phase and combines epoxy resin or thermosetting resin as a matrix material to form a composite material with high strength and good toughness. The fiber volume fraction of the composite material is controlled at 55%-65%, and the resin matrix accounts for 35%-45%.
[0030] Carbon fiber composites (CFRP) are used in high-performance vehicles because of their low density (1.6 g / cm 3 ) and extremely high specific strength, which enables this material to effectively reduce weight in the suspension system while also having excellent fatigue performance.
[0031] Glass fiber composites (GFRP) are suitable for mass production of vehicles, with low cost and good mechanical properties, with a density of about 2.0-2.5g / cm 3 Its superior impact resistance and durability are suitable for the suspension systems of mid- and low-end models.
[0032] 1.2 Fiber layup structure design
[0033] Fiber lamination design is one of the key factors affecting the performance of composite materials. By laying fibers at different angles, it is possible to efficiently respond to loads in different directions such as tension, bending, and shear. Laying design includes:
[0034] 0° layer: mainly used to bear the tensile load along the longitudinal direction of the spring and ensure the longitudinal stiffness of the spring.
[0035] ±45° layer: used to improve the torsional rigidity and shear strength of the spring and prevent excessive deformation of the spring when subjected to lateral loads.
[0036] 90° layer: used to enhance the lateral strength and ensure that the spring still has sufficient strength and stiffness when subjected to lateral or vertical loads.
[0037] By combining these plies in different directions, the composite spring can maintain stable mechanical properties under multi-directional complex loads and optimize its stress distribution.
[0038] 1.3 Preparation process
[0039] 1.3.1 Prepreg preparation
[0040] The preparation of composite materials first requires pre-impregnation of carbon fiber or glass fiber into a resin matrix. This step ensures a tight bond between the fiber and the resin by controlling the fiber content, the viscosity of the resin (200-300mPa·s) and the uniformity to form a high-quality prepreg.
[0041] 1.3.2 Hot Pressing
[0042] The prepared prepreg is placed in the mold in sequence according to the designed ply angles (0°, ±45°, 90°). The mold is heated to 180°C and a pressure of 3-5MPa is applied for 1-2 hours using a hot pressing process to cure the composite material under high temperature and high pressure. This process ensures that the interlayer bonding of the material is strong and the geometric shape of the cured material meets the design requirements.
[0043] 1.3.3 Fiber winding
[0044] For spring steels with special shapes, computer numerical control fiber winding technology is used. This process can accurately control the fiber winding angle (usually ±45°) and tension (10-15N) to ensure that the fiber is evenly distributed on the spring geometric surface to avoid stress concentration or fiber shedding caused by uneven tension.
[0045] 1.3.4 Surface coating
[0046] In order to improve the corrosion resistance of composite spring steel, the present invention adopts nano coating technology, such as chemical vapor deposition (CVD) or physical vapor deposition (PVD) process, to form a dense protective film on the surface of the spring. The coating material is Ti N or Si C, and the coating thickness is controlled in the range of 5-10 μm. Through the nano coating, the spring steel has excellent durability in high humidity or corrosive environment.
[0047] 2. High entropy alloy spring steel
[0048] 2.1 High entropy alloy material design
[0049] High entropy alloy is an alloy system composed of multiple metal elements (usually five or more) in equal proportions. High entropy alloys based on the CoCrFeMnNi system have excellent mechanical properties and corrosion resistance, and are particularly suitable for use under complex working conditions.
[0050] Cobalt (Co) and nickel (Ni) can significantly improve the toughness and corrosion resistance of the alloy, especially in humid and salt spray environments.
[0051] Chromium (Cr) provides additional corrosion resistance and prevents corrosion by forming a dense protective oxide film.
[0052] Iron (Fe) and manganese (Mn) improve the strength of the alloy while ensuring the ductility and toughness of the material.
[0053] By controlling the content of each element (by mass percentage, Co: 15%-25%, Cr: 15%-20%, Fe: 20%-25%, Mn: 15%-25%, Ni: 10%-15%) and adding trace amounts of molybdenum (Mo) and vanadium (V) elements (0.1%-0.5% each), a high-entropy alloy material with high strength, fatigue resistance and corrosion resistance can be formed.
[0054] 2.2 Preparation process
[0055] 2.2.1 Vacuum induction melting
[0056] The smelting process of high entropy alloy is carried out in a vacuum environment to prevent metal oxidation. The specific steps are:
[0057] Co, Cr, Fe, Mn, Ni and trace elements are weighed in proportion and added into the vacuum induction furnace.
[0058] Heat to 1600-1700℃ to ensure that all elements are fully melted, and stir evenly to ensure the uniformity of the alloy composition.
[0059] After smelting, the primary alloy billet is formed through continuous casting or die casting. During the cooling process, the cooling rate is controlled at 5-10℃ / s to optimize the grain structure and improve the toughness and fatigue strength of the material.
[0060] 2.2.2 Heat treatment
[0061] During the preparation process, high entropy alloys are subjected to isothermal quenching treatment to improve the microstructure and properties of the material. The temperature of isothermal quenching is controlled at 300°C, kept for 1 hour, and then slowly cooled to room temperature. This step refines the grains and optimizes the phase structure, giving the alloy better toughness and fatigue resistance.
[0062] 2.2.3 Surface quenching and cladding
[0063] The present invention uses laser surface quenching treatment on the surface of the high entropy alloy. Through laser heating, the surface layer is quickly cooled to form a high hardness area, thereby enhancing the surface fatigue resistance and wear resistance of the material.
[0064] In addition, a layer of corrosion-resistant and wear-resistant CoCrNi-based alloy cladding layer is deposited on the surface of the high-entropy alloy spring by laser cladding technology. The thickness of the cladding layer is 50-100μm. By adjusting the laser power (800W) and scanning speed (10mm / s), the cladding layer is well combined with the base material and the surface is uniform and defect-free.
[0065] 3. Performance testing and verification
[0066] 3.1 Fatigue performance
[0067] The composite material and high entropy alloy spring steel in the present invention were subjected to multiple dynamic fatigue tests with a loading frequency of 10 Hz and a maximum load of 50 kN. The number of fatigue cycles was set to 10 6 The test simulated the actual working state of the car under long-term and high-frequency loads. The test results showed that the fatigue life of the spring steel of the present invention was increased by about 2 times compared with the traditional steel.
[0068] 3.2 Corrosion resistance
[0069] The prepared composite material and high entropy alloy spring steel were placed in a salt spray corrosion environment of 5% sodium chloride solution for 1000 hours, and the surface corrosion was observed using a scanning electron microscope (SEM). The test results show that the nano-coating on the surface of the composite material and the cladding layer of the high entropy alloy effectively inhibited corrosion, and the corrosion rate was reduced by more than 50%.
[0070] 3.3 High and low temperature performance
[0071] Mechanical property tests were carried out on the spring steel at -40°C and 200°C. The results showed that the spring steel of the present invention can maintain stable strength and toughness in both low and high temperature environments, ensuring the reliability of the automobile suspension system under extreme conditions.
[0072] Example 1: High-strength carbon fiber composite spring steel
[0073] Step 1:
[0074] Fiber prepreg preparation
[0075] T300 grade carbon fiber is used, with a fiber volume fraction of 60%, and the resin matrix is epoxy resin, accounting for 40%. The resin viscosity is controlled at 250mPa·s, and the fiber prepreg process is carried out at room temperature.
[0076] Step 2:
[0077] Hot Press Forming
[0078] The prepreg was laid in the mold in the order of 0°, ±45° and 90°. The mold was preheated to 180°C, 4MPa pressure was applied, and the mold was kept warm for 90 minutes for curing. After curing, it was cooled at room temperature to obtain a preliminarily formed carbon fiber composite spring steel.
[0079] Step 3:
[0080] Surface treatment
[0081] The surface is coated with a TiN nano-coating by chemical vapor deposition (CVD) method with a coating thickness of 8 μm. The nano-coating enhances the corrosion resistance and wear resistance of the composite material.
[0082] Comparative Example 1: Traditional high carbon steel spring
[0083] Step 1:
[0084] Material selection
[0085] Use traditional 60Si2Mn high carbon steel with a carbon content of 0.6% and undergo ordinary quenching and tempering treatment.
[0086] Step 2:
[0087] Quenching and tempering
[0088] The steel is heated to 850°C, water quenched, and then tempered at 450°C to obtain a high carbon steel spring. There is no additional surface treatment and it is directly applied.
[0089] Example 2: High-strength glass fiber composite spring steel
[0090] Step 1:
[0091] Fiber prepreg preparation
[0092] E-grade glass fiber is used, with a fiber volume fraction of 55%, and the resin matrix is a thermosetting resin, accounting for 45%. The resin viscosity is 220mPa·s.
[0093] Step 2:
[0094] Hot Press Forming
[0095] The prepreg was laid at an angle of 0° and ±45°, with a thickness of 0.6 mm per layer, a mold temperature of 180°C, a pressure of 3.5 MPa, and a curing time of 2 hours. The prepreg was then demoulded at room temperature to obtain a glass fiber composite spring steel.
[0096] Step 3:
[0097] Surface treatment
[0098] A layer of SiC nano-coating with a thickness of 7 μm is deposited on the surface using physical vapor deposition (PVD) technology. The coating enhances the fatigue resistance of the composite material.
[0099] Comparative Example 2: High manganese steel spring
[0100] Step 1:
[0101] Material selection
[0102] The spring is made of traditional high manganese steel (65Mn). The carbon content is 0.65%, and the mechanical properties are mainly improved through heat treatment.
[0103] Step 2:
[0104] Heat Treatment
[0105] After heating to 830°C, oil quenching is performed and then tempering is performed at 300°C. This material has poor corrosion resistance without additional surface treatment.
[0106] Example 3: High Entropy Alloy Spring Steel
[0107] Step 1:
[0108] High Entropy Alloy Ingredients
[0109] Weigh cobalt (Co): 20%, chromium (Cr): 17%, iron (Fe): 23%, manganese (Mn): 20%, nickel (Ni): 12%, and trace amounts of molybdenum (Mo) and vanadium (V) of 0.3% each by mass.
[0110] Step 2:
[0111] Vacuum Induction Melting
[0112] The high entropy alloy billet is obtained by heating to 1650°C in a vacuum furnace, performing vacuum induction melting, stirring evenly, and then continuously casting.
[0113] Step 3:
[0114] Heat Treatment
[0115] After isothermal quenching at 300°C and keeping warm for 1 hour, the steel was cooled to room temperature and then a 80μm thick CoCrNi-based alloy coating was formed on the surface using laser cladding technology to improve its corrosion resistance and fatigue resistance.
[0116] Comparative Example 3: Traditional Stainless Steel Spring
[0117] Step 1:
[0118] Material selection
[0119] Use traditional 304 stainless steel, the main component of which is Fe-Cr-Ni alloy, with 18% chromium and 8% nickel.
[0120] Step 2:
[0121] Cold Roll Forming
[0122] The springs are produced by cold rolling process, using standard quenching and tempering process without surface hardening treatment.
[0123] Comparative Experimental Design
[0124] In order to verify the superiority of the automobile suspension spring steel of the present invention, the following comparative experiment was designed to test the fatigue life, corrosion resistance and lightweight performance of different spring materials.
[0125] Experimental conditions:
[0126] Fatigue test: On a fatigue testing machine, the loading frequency is 10Hz, the maximum load is 50kN, and 1 million cycles are performed, and the number of fatigue cycles before the spring breaks is recorded.
[0127] Corrosion resistance test: Carry out a 1000-hour corrosion test in a salt spray environment of 5% NaCl solution to detect the corrosion depth of the spring surface.
[0128] Weight test: Measure the weight of each spring, calculate its mass percentage, and compare lightweight performance.
[0129] Experimental results:
[0130]
[0131] According to experimental comparison:
[0132] 1. Fatigue performance comparison: The fatigue life of the composite springs of Examples 1 and 2 is significantly better than that of the traditional steel springs of Comparative Examples 1 and 2. The high strength and lightweight properties of carbon fiber and glass fiber enable the spring to maintain a long service life under high-frequency loads. The high-entropy alloy of Example 3 also exhibits high fatigue performance, which is better than traditional stainless steel springs.
[0133] 2. Corrosion resistance comparison: The spring materials of the embodiments are all surface treated, and the corrosion resistance is significantly improved. In particular, the high entropy alloy spring of embodiment 3 has the smallest corrosion depth of only 5 μm, which is significantly better than the high carbon steel and stainless steel materials in the comparative example.
[0134] 3. Comparison of lightweight performance: The composite material spring (Example 1 and Example 2) is about 30% lighter than the traditional steel spring, showing a significant lightweight advantage. This plays an important role in reducing the weight of the vehicle and improving fuel economy.
[0135] In summary, the automobile suspension spring steel of the present application exhibits excellent performance in fatigue life, corrosion resistance and lightweight performance by combining high-strength composite materials with high-entropy alloys, and has significant technical advantages over traditional high-carbon steel, manganese steel and stainless steel springs.
[0136] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An automobile suspension spring steel, characterized in that: Includes the following materials: High-strength composite spring steel, wherein the fiber is carbon fiber or glass fiber, the resin matrix is epoxy resin or thermosetting resin, the fiber volume fraction is 55%-65%, the resin matrix is 35%-45%, and the fiber layer laying angles are 0°, ±45° and 90°; High entropy alloy spring steel, its alloying elements include cobalt, chromium, iron, manganese, and nickel, and the content of each element by mass percentage is: cobalt 15%-25%, chromium 15%-20%, iron 20%-25%, manganese 15%-25%, nickel 10%-15%, and trace elements molybdenum and vanadium, whose content is 0.1%-0.5%.
2. The automobile suspension spring steel according to claim 1, characterized in that: The surface of the high-strength composite material spring steel is provided with a nano coating with a thickness of 5-10 μm, and the coating is a TiN or SiC nano material.
3. The automobile suspension spring steel according to claim 1, characterized in that: The surface of the high entropy alloy spring steel is processed by laser cladding technology, the thickness of the cladding layer is 50-100 μm, and the cladding material is a CoCrNi-based alloy.
4. A method for preparing automobile suspension spring steel, according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Preparation of high-strength composite spring steel: carbon fiber or glass fiber and epoxy resin matrix are mixed in a volume fraction ratio of 55%-65% and 35%-45%, layered at angles of 0°, ±45° and 90°, and hot-pressed to obtain composite spring steel; 2) preparing high entropy alloy spring steel: weighing raw materials of cobalt, chromium, iron, manganese, nickel and trace amounts of molybdenum and vanadium according to mass percentage, and melting them by vacuum induction melting and casting process to form a high entropy alloy billet; 3) Heat treatment and surface strengthening: The high entropy alloy billet is subjected to isothermal quenching and laser surface cladding treatment to enhance the surface strength and corrosion resistance of the material.
5. The method for preparing automobile suspension spring steel according to claim 4, characterized in that: The resin viscosity is controlled at 200-300 mPa·s, the temperature of hot pressing is controlled at 180° C., the pressure is 3-5 MPa, and the curing time is 1-2 hours.
6. The method for preparing automobile suspension spring steel according to claim 4, characterized in that: The fiber winding process uses a CNC fiber winding device to control the winding angle to be ±45° and the winding tension to be within the range of 10-15N to ensure uniform laying of the fibers.
7. The method for preparing automobile suspension spring steel according to claim 4, characterized in that: The vacuum induction melting temperature of the high entropy alloy is 1600-1700°C, and the cooling rate is controlled at 5-10°C / s to optimize the grain structure of the alloy.
8. The method for preparing automobile suspension spring steel according to claim 4, characterized in that: The high entropy alloy is isothermal quenched at 300° C. for 1 hour and then slowly cooled to room temperature.
9. The method for preparing automobile suspension spring steel according to claim 4, characterized in that: In the laser cladding process, the laser power is 800W, the scanning speed is 10mm / s, and the cladding thickness is 50-100μm.
10. The method for preparing automobile suspension spring steel according to claim 4, characterized in that: The surface nano coating is formed by physical vapor deposition, and the coating thickness is controlled at 5-10 μm.